10 questions with…IAIN MILLAR. (Bookseller, 2010)
An interview with Iain Millar, marketing manager of British publishing firm Quercus, is presented. Millar reveals that he once wanted to be a computer programmer when he was younger. He considers managing the electronic book list of the company as one of the digital publishing challenges that his job covers. He recommends getting a lot of general publishing experience before focusing on one discipline to someone who is just starting out in the book industry.